Cognitive processing, PSTD symptoms, and the mediating role of posttraumatic cognitions - Mordeno, Imelu G.; Nalipay, Ma. Jenina N.; Saavedra, Rhea Lina J. (2015)
The association between cognitive processing strategies and
posttraumatic stress disorder (PTSD) symptoms has been demonstrated
in a number of studies. However, the process of how cognitive processing
determines PTSD symptoms is yet to be understood. The present study
aims to clarify the relationship between cognitive processing and PTSD
symptoms by examining the mediating role of posttraumatic cognitions
in a sample of natural disaster survivors. The participants of the present
study include 632 individuals who were directly affected by typhoon
Haiyan. Findings of the study reveal that negative cognitions about the
self mediated the relationship between cognitive processing of trauma
(i.e., denial, regret, and resolution/acceptance), and PTSD symptom
severity. Denial and regret were related to more severe PTSD symptoms
through increased negative cognitions about the self. On the other
hand, resolution/acceptance was associated with lesser PTSD symptom
severity through decreased negative self-cognitions.
Keywords: Post-traumatic stress disorder; Cognitive learning